Vocational college students’ common errors in EFL speaking performance - Naria Fitriani; Said Iskandar Zulkarnain (Studies in English Language and Education, 2019)
This research aims to find out the common errors made by students studying at one of the vocational colleges in Banda Aceh, Indonesia. The students’ opinions on their experiences of learning English, particularly in speaking, were also explored. This qualitative-quantitative research design was conducted by collecting some recordings of the students’ speaking performance, and distributing questionnaires on the process of teaching and learning EFL to be filled in by the participants. In the analysis, the data from the recordings were coded, transcribed, described and displayed in accordance with the students’ error items. Meanwhile, the analysis of the questionnaire employed a simple percentage calculation. From the speaking performance, the students in the speaking class produced two types of common errors, i.e. pronunciation and grammar errors. The common errors in their English pronunciation vary between the vowel and the consonant. The errors in vowel production were produced the most. Meanwhile, 70% of the students made errors in grammar on language tense and some on plural morphemes. From the questionnaire, it was revealed that even though the students tried to speak English well, all of them were aware and agreed that they made grammatical errors when speaking English.